Ordinance no. 27, §§ 17-18, GRANTS PASS, REVISED ORDINANCES OF THE CITY (Rogue River Courier Print 1894) (Approved 1889). - (:unkn) unknown (My University, 1889)
Imposed a 10 dollar license fee on shooting galleries
Keywords: SHOOTING RANGES OR GALLERIES